Basic Analysis of the Exercise of Judicial Power (Integration of Islamic Law and Positive Law) - Nabilah, Wardatun; Shodiq, Ja'far; Rizal, Deri (Universitas Islam Lamongan, 2024)
Abstract This study aims to see the form of integration of Risalah al-Qadha as Islamic judicial principles and the principle of administering Indonesian Judicial Authority. This study uses a qualitative method with a descriptive approach to the analysis of the documents used in the study, namely Risalah al-Qadha and Law No. 48 of 2009 regarding Judicial Authority. This study argues that Indonesia's modern judiciary has undergone a transformation. One of this is the application of normative Islamic law to positive Islamic law. The judiciary (judiciary) functions to carry out all legal provisions consequently so as to create fair laws. Similarly, the importance of sulthah qadhaiyyah (judicial institution) is a necessity and an absolute condition that must be fulfilled. The contextualization of Islamic judicial principles which is manifested in the principle of administering Indonesian Judicial Authority in the principle of a free and impartial judiciary, the judiciary is democratic and equal in law and transparent.